Air-kerma to Hp(0.07), Hp(3), and Hp(10) conversion coefficients for monoenergetic photons. (June 2020) - Al Kanti, Hassan; El Hajjaji, O.; El Bardouni, T.; Boukhal, H.
Abstract: This work aims for calculating a new set of the personal dose equivalent conversion coefficients H p ( d)/Kair when d = 0.07, 3, and 10 mm, for monoenergetic photons beams ranged from 0.015 to 10 MeV, which have incident on ICRU slab phantom for H p (0.07) and H p (10) and cylindrical phantom for H p (3). The new cylindrical phantom of the ORAMED project was proposed for calculating the eye lens dose equivalent as a cylinder much better approximates the form of a head than a slab. The calculations were carried out with MC and an analytical fit is applied to the data. Our results are found in a good agreement with those previously published, with a local difference less than 1.5%. We have concluded that new analytical fits provide a suitable method for determining conversion coefficients for discrete incident such as MC. Highlights: The maximum dose is in the depth 0.07, 3 and 10 mm at the energies 0.06 to 0.1 MeV, so overestimate the protection quantity at that energies. A new analytical fit provides a suitable method for determining conversion coefficients. The obtained results are found in a good agreement with those previously published.